Analisis Sentimen dan Jaringan Pada Video Youtube Malaka “Memahami Danantara dengan Mudah” - Fathan Auzan Abdullah; Gema Nusantara Bakry; Siti Fatimah Zahrah Fibaeti (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This article aims to analyze the interaction patterns and distribution of sentiment in user comments on the Malaka Project YouTube video entitled “Memahami Danantara dengan Mudah”. This study uses a combined approach between sentiment analysis and Social Network Analysis (SNA) to gain a comprehensive understanding of the public response to the educational content. Data were collected using the YouTube Data API and analyzed quantitatively using Google Colab and visualized through the Gephi application. The results of the study show that the network formed has a diameter of 2, with density and reciprocity values of 0.000000 each, and a very low centralization of 0.0001861. This finding indicates that interaction between users in the comments olumn is very minimal and one-way, without any meaningful two-way communication. However, the modularity value of 0.735 indicates that the comments form certain clusters that represent communities with similar interests or discussion topics. In terms of sentiment, positive comments dominate with a total of 1,843 uploads, followed by neutral comments of 2,824 and negative comments of 1,217. This shows that despite low user interaction, the perception of the content is generally positive and well received by the majority of viewers.